Changes in inmates' substance use and dependence from pre-incarceration to one year post-release. (September 2016) - Tangney, June P.; Folk, Johanna B.; Graham, David M.; Stuewig, Jeffrey B.; Blalock, Daniel V.; Salatino, Andrew; Blasko, Brandy L.; Moore, Kelly E.
Abstract: Purpose: To assess changes in inmates' misuse of substances from pre- to post-incarceration. Methods: In Study 1, professionals ( n = 162) and laypersons ( n = 50) predicted how jail inmates' substance misuse would change from pre-incarceration to post-release. In Study 2, a longitudinal study of 305 jail inmates, we examined actual changes in substance use and dependence from pre-incarceration to the first year post-incarceration, as well as whether changes varied as a function of demographic, criminal justice, treatment, and personality factors. Results: Professionals and laypersons predicted little change in substance misuse whereas, in fact, inmates' frequency of substance use and dependence decreased substantially from pre-incarceration to post-release. Sharper decreases were observed for inmates who were female, younger, more educated, serving longer sentences, enrolled in substance abuse treatment, high in shame-proneness, and low in criminogenic thinking. Race, first time incarceration, transfer to other correctional facilities, mandated community supervision (probation), and guilt-proneness did not predict changes in substance use or dependence. Conclusions: Although substance misuse decreased, this remains a population high in need of substance abuse treatment both upon arrest and at one year post-incarceration; 60% of former inmates met at least one DSM-IV criterion for substance dependence at one year post-release. Highlights: In Study 1, professionals from Psychology and Criminology ( n = 162) and laypersons ( n = 50) predicted that jail inmates' substance misuse would change little from pre-incarceration to post-release. In Study 2, a longitudinal study of 305 jail inmates, frequency of substance use and dependence decreased substantially from pre-incarceration to one-year post-release. Sharper decreases were observed for inmates who were female, younger, more educated, serving longer sentences, enrolled in substance abuse treatment, high in shame-proneness, and low in criminogenic thinking. Race, first time incarceration, transfer to other correctional facilities, mandated community supervision (probation), and guilt-proneness did not predict changes in substance use or dependence. Although substance misuse decreased, this remains a population high in need of substance abuse treatment both upon arrest and at one year post-incarceration; 60% of former inmates met at least one DSM-IV criterion for substance dependence at one year post-release.